A retrospective study of pembrolizumab combined with XELOX regimen in the treatment of advanced gastric cancer - FENG Huizhi, LIU Jingmei, BU Xiaoqian (Zhongguo aizheng zazhi)
Background and purpose: Despite the significant advancements that have been made in the treatment of gastric cancer, there are still problems such as poor prognosis and low five-year survival rate in advanced gastric cancer. Therefore, exploring effective treatment options remains a key focus of clinical research. As a new type of immune checkpoint inhibitor, the clinical efficacy and safety of pembrolizumab still need to be confirmed by extensive research. Therefore, this study conducted regression analysis of the effect of pembrolizumab combined with XELOX regimen in the treatment of advanced gastric cancer, providing a reference for clinical treatment. Methods: Clinical data of patients with advanced gastric cancer who were admitted to Shanxi Province Cancer Hospital from March 2020 to August 2022 were retrospectively collected. Inclusion criteria: patients with HER2-negative, untreated advanced gastric cancer or adenocarcinoma of the esophagogastric junction, confirmed by clinical histopathological examination and meeting relevant diagnostic criteria; TNM stage Ⅳ; age ≥20 years; expected survival ≥6 months; no severe organ damage before treatment; Karnofsky score >60; patients with complete clinical data. Exclusion criteria: patients with concurrent major organ dysfunction; hypothyroidism or hyperthyroidism; blood or coagulation disorders; autoimmune diseases; lactating or pregnant women; individuals with mental illnesses or a history of mental illness; those with concurrent other malignancies; those with severe liver or kidney dysfunction; patients with incomplete clinical data. Based on the inclusion and exclusion criteria, 91 patients with advanced gastric cancer were selected. Among them, 45 received XELOX regimen treatment (control group), and 46 received pembrolizumab combined with XELOX regimen treatment (observation group). After establishing the database, one patient in the observation group was found to have logical errors in their treatment information and was therefore excluded. Ultimately, 90 patients were included in the study, with 45 in each of the control and observation groups. The efficacy, median overall survival (OS), median progression-free survival (PFS), toxic side effects, improvement in quality of life, and levels of carcinoembryonic antigen (CEA), carbohydrate antigen 19-9 (CA19-9), Escherichia coli, Bifidobacterium and Lactobacillus before and after treatment were compared between the two groups. This study was approved by the ethics committee of Shanxi Province Cancer Hospital (ethics number: KY2023081). Results: After treatment, the proportion of progressive disease (PD) in the observation group was 20.0% (9/45), which was lower than that in the control group (40.0%, 18/45). However, there was no significant difference between the two groups in proportion of stable disease (SD), complete response (CR) and partial response (PR) (P>0.05). The improvement rate of quality of life in the observation group after treatment was 60.0% (27/45), which was higher than that in the control group, with a rate of 37.8% (17/45) (P<0.05). The median OS and PFS in the observation group were longer compared with the control group (P<0.05). After treatment, the levels of CEA and CA19-9 in peripheral blood of the observation group were lower compared with the control group (P<0.05). After treatment, the number of Escherichia coli was lower in the observation group than in the control group, while the numbers of Bifidobacterium and Lactobacillus were higher (P<0.05). There was no significant difference in the incidence of nausea and vomiting, diarrhea, leukopenia, rash, liver function damage between the two groups (P > 0.05). Conclusion: The combination of pembrolizumab and XELOX regimen can regulate the expression levels of tumor markers in patients with advanced gastric cancer, prevent disease progression, improve patient quality of life, and help maintain intestinal microecology balance.